Antibacterial activity of graphene oxide. - Hu, Ming. (2012)
Healthy and environmental issues are the most concerned issues around the globe. Graphene-oxide (GO) material has shown potential in antibacterial activity. However, the impact of GO must be exhaustively evaluated before its further application. To better understand its antibacterial mechanism, antibacterial activity of GO toward a bacterial model-E.coli was conducted. The antibacterial activity of GO was measured by counting methods and GO eventually shows a strong antibacterial activity against E.coli. Scanning electron microscope (SEM) and Atomic force microscopy (AFM) combined display the direct contacts with grapheme nanosheets disrupt bacterial membrane. The death rate was measured and in addition to that, we also test other factors, such as pH, salt concentration in medium and illumination, to check whether they have an influence on antibacterial effect. The result shows that pH is inversely proportional to the antibacterial of GO as well as salt concentration in medium. The illumination, however, has minimal effect on the antibacterial activity.